Pimentas do gênero Capsicum cultivadas em Roraima, Amazônia Brasileira. I. Espécies domesticadas - Barbosa, Reinaldo Imbrozio; Luz, Francisco Joaci de Freitas; Nascimento Filho, Herundino Ribeiro do; Maduro, Cice Batalha (Acta Amazonica, 2002)
Domesticated pepper species of the genus Capsicum cultivated in Roraima State, northern Brazilian Amazonia were surveyed. We collected 163 accessions of this group among small farmers (colonists) and indigenous communities. Capsicum chinense Jacq. (76.7%) was the species with largest number of accessions, followed by C. frutescens L. (9.8%), C. annuum L. (8.0%) and C. baccatum v. pendulum Wild. (5.5%). Main fruit shapes were "long" (42.9%) and "oval" (27.0%). C. chinense presented the largest diversity in forms while the other species showed mainly the "long" shape. The predominant color of mature fruits was red (64.4%). C. chinense presented a better distribution among the basic colors (yellow - 44.8% and red - 55.2%), without considering the different tonalities of individual accessions (orange, dark red etc). The sensorial pungency leves were "high" (62.6%), followed by "medium" (16.0%), "low" (15.3%) and "very high" (6.1%). Within the 105 accessions of red coloration 67.6% possessed "high" or "very high" pungency. C. chinense accessions popularly known as "murupi" and "olho-de-peixe", together with "malagueta" (C. frutescens), are the most traditional types consumed among local indige-nous communities.
Capsicum Peppers Cultivated in Roraima, Brazilian Amazonia. I. Domestic Species
Keywords: Capsicum; Roraima; Pepper; Amazon; Capsicum; Roraima; Pimenta; Amazônia